2016
DOI: 10.21608/jpp.2016.45548
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Waterdeficit on Seed Yield and Prolinecontent in Some Faba Bean Genotypes

Abstract: Drought stress is one of the most serious problems for agriculture production and sustainability. This study was carried out to investigate seed yield and its components in addition to estimate free proline content in leaves of nine faba bean genotypes with different types grown under three water regimes (well-watered, mild and severe drought).A field experiment was laid out in split plot with three replications during two growing seasons, 2013/14 and 2014/15. The results indicated that drought had pronounce n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…The differences between the three (ASMD) treatments on WUE were significant in both seasons. The obtained results are in full agreement with those reported by Ekebafe et al(2011), Chandrika et al (2014 and El-Harty (2016).…”
Section: Faba Bean Yield Response To Various Available Soil Moisture Depletion and Polyvinyl Alcohol Concentrations Treatmentssupporting
confidence: 93%
See 1 more Smart Citation
“…The differences between the three (ASMD) treatments on WUE were significant in both seasons. The obtained results are in full agreement with those reported by Ekebafe et al(2011), Chandrika et al (2014 and El-Harty (2016).…”
Section: Faba Bean Yield Response To Various Available Soil Moisture Depletion and Polyvinyl Alcohol Concentrations Treatmentssupporting
confidence: 93%
“…El-Harty (2015) showed that drought had pronounced negative effects on yield and its components for all faba bean yield characters. El-Harty, (2016) identified a decrease in Faba bean traits with water deficit except WUE which was highest under moderate stress.…”
Section: Introductionmentioning
confidence: 94%
“…The importance of additive genetic action in controlling these traits was previously mentioned by Abdelmula (2006), EL-Harty (2006), Ibrahim (2010), , Farag and Afiah (2012), El-Banna et al, (2014), EL-Harty (2016), andBishnoi et al, (2018). On the other hand, the non-additive genetic variance was previously reported to be the most prevalent for seed yield plant -1 by Obiadalla et al, (2013), El-Harty et al, (2016 and El-Abssi et al (2019) No. of branches plant -1 by Sattar et al, (2012); and Ashrei et al (2014) ; For 100-seed weight by Abd-Elrahman et al, (2012) and Farag and Afiah (2012).…”
Section: El-bathmentioning
confidence: 79%